Recent Advances in the Sustainable Synthesis of Quinazolines Using Earth-Abundant First Row Transition Metals - Zaib, Sumera; Khan, Imtiaz (Current Organic Chemistry, 2020)
Achieving challenging molecular diversity in contemporary chemical synthesis remains a formidable hurdle, particularly in the delivery of diversified bioactive heterocyclic pharmacophores for drug design and pharmaceutical applications. The coupling methods that combine a diverse range of readily accessible and commercially available pools of substrates under the action of earth-abundant first row transition metal catalysts have certainly matured into powerful tools, thus offering sustainable alternatives to revolutionize the organic synthesis. This minireview highlights the successful utilization of the catalytic ability of the first row transition metals (Mn, Fe, Ni, Cu) in the modular assembly of quinazoline heterocycle, ubiquitously present in numerous alkaloids, commercial medicines and is associated with a diverse range of pharmacological activities. The broad substrate scope and high functional group tolerance of the targeted methods were extensively explored, identifying the future strategic advances in the field. The investigation will also be exemplified with mechanistic studies as long as they are deemed necessary.
Keywords: quinazolines